The validity of Prometheus as ethical paradigm in "The Heretic", by Miguel Delibes - Lorenzo García, Esther (Amaltea. Revista de Mitocrítica, 2012)
The defence of religious freedom and, by extension, of freedom of thought, is the idea that led Miguel Delibes to write The Heretic, his last novel. In order to develop this subject, the narrator uses the mythologem of the rebel who, spurred by an imperative of reason or his own morals, dares to go beyond the limits allowed by law and, as a consequence, must face hard punishment. The large number of episodes and symbolic elements related to the image of the Titan in his version of tragic hero justifies, in my view, an approach from the myth to this highly praised but seldom studied novel. This contribution will detail how the main mythemes of Aeschylus’ Prometheus – rebellion, philanthropy, freedom, endurance… – are assimilated from the viewpoint of Christian humanism and to what extent they express, beyond religion, their status of objective values in contrast to the relativistic concepts about human being and also in contrast to the new threat of fundamentalism.